Assessing and Modelling Domestic Water Consumption Behavior - Raja Ahmad, Raja Adzrin; Samsudin , Syamsyul; Azmi, Nurul Azlin; Md Yatim, Nurul Huda (Information Management and Business Review, 2024)
The UNICEF predicts severe water shortages and water scarcity worldwide. According to a water resources study conducted from 2000 to 2050, Malaysia is susceptible to potential water shortages in specific regions. These projections emphasized the importance of sustainable water management practices and proactive measures to mitigate potential water scarcity. It becomes crucial for Malaysia to implement effective strategies to address this issue. Therefore, this study aims to identify factors that influence sustainable water consumption behavior (SWCB) and establish a model for understanding consumer behavior in consuming water for domestic usage. Using the prominent theory of planned behavior (TPB) and reviewing the prior literature, this paper proposes a model to assess SWCB to understand consumer behavior on the water. This study found that attitudinal predictors significantly influence the SWCB. These predictors influence consumers’ motivation, engagement, and views that may influence water intention and consumption behavior. Then, consumer intention mediates the relationship between attitudinal predictors and SWCB as it will evaluate consumers’ favorable and unfavorable actions. Moreover, the model also found that socio-demographic traits (gender, household size, and income level) influence SWCB. These factors are the critical variables that significantly influence the SWCB. This paper contributes to policy implementation by modelling SWCB to help policymakers and urban planners develop effective policies and strategies to address water management challenges. By considering the drivers and barriers to sustainable behavior, policymakers can design targeted interventions, provide incentives, and implement regulations that promote water conservation at the household level.